Comparison of creatinine and cystatin C for estimation of glomerular filtration rate in pediatric patients after Fontan operation. (16th April 2019) - Kirelik, Danielle; Fisher, Mark; DiMaria, Michael; Soranno, Danielle E.; Gist, Katja M.
Abstract: Background: There are several limitations when using creatinine to estimate glomerular filtration rate, especially in children with chronic medical conditions who are at high risk of kidney dysfunction. Cystatin C has been the recent focus of research as a replacement biomarker for creatinine. Our objective was to compare the 2 biomarkers in pediatric single‐ventricle heart disease patients who have undergone the Fontan operation. We hypothesized that there would be poor correlation and agreement between the 2 estimates of renal function. Methods: This was a single center retrospective chart review of 20 patients who had previously undergone Fontan operation. Demographic and clinical data were collected from medical records. Blood samples were collected as part of routine clinical care and simultaneously measured for serum creatinine and cystatin C. Glomerular filtration rate was calculated using the creatinine‐based bedside Schwartz formula and cystatin C‐based Zapatelli equation. Spearman correlation and Bland‐Altman analysis were used to assess correlation and agreement. Results: The median Schwartz‐derived estimated glomerular filtration rate was 98.94 mL/min/1.73 m 2 while the median Zappitelli‐derived estimated glomerular filtration rate was 84.76 mL/min/1.73 m 2 . The mean difference was −19.27 suggesting poor agreement. There was weak to moderate correlation between the Schwartz and cystatin C estimated glomerular filtration rate. Conclusion: The bedside Schwartz formula may be an overestimate of glomerular filtration rate in pediatric single‐ventricle heart disease patients who have undergone the Fontan operation. While larger studies are necessary, cystatin C is a promising biomarker to replace creatinine and better estimate kidney function in this population.